2022
DOI: 10.1038/s41467-022-28906-4
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic holey graphene aerogel fibers enable highly efficient moisture capture, heat allocation and microwave absorption

Abstract: Aerogel fibers have been recognized as the rising star in the fields of thermal insulation and wearable textiles. Yet, the lack of functionalization in aerogel fibers limits their applications. Herein, we report hygroscopic holey graphene aerogel fibers (LiCl@HGAFs) with integrated functionalities of highly efficient moisture capture, heat allocation, and microwave absorption. LiCl@HGAFs realize the water sorption capacity over 4.15 g g−1, due to the high surface area and high water uptake kinetics. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
194
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(195 citation statements)
references
References 61 publications
(86 reference statements)
1
194
0
Order By: Relevance
“…As apparent from Figure 8, with the increase of temperature, the adsorption rate accelerates and the equilibrium adsorption amount increases (Davarpanah et al, 2022). Therefore, it can be concluded that the process of C-SAA and C-SAAoa defluorination is a heat absorption process (Hou et al, 2022). order kinetic model and their associated dynamic models well.…”
Section: Adsorption Kineticsmentioning
confidence: 78%
“…As apparent from Figure 8, with the increase of temperature, the adsorption rate accelerates and the equilibrium adsorption amount increases (Davarpanah et al, 2022). Therefore, it can be concluded that the process of C-SAA and C-SAAoa defluorination is a heat absorption process (Hou et al, 2022). order kinetic model and their associated dynamic models well.…”
Section: Adsorption Kineticsmentioning
confidence: 78%
“…S7, ESI †). Water vapor sorption kinetics of cl-SP beads can be expressed using eqn (1) and ( 2), 23,39,42…”
Section: Water Vapor Sorption and Desorption At Indoor Conditionsmentioning
confidence: 99%
“…33,34 So far, the efforts to seek high-performing hygroscopic materials with rapid water vapor sorption, high water vapor uptake, low regeneration temperature and sustainable energy input are rising. [35][36][37][38][39][40][41][42][43][44][45] Incorporation of emerging desiccants (i.e., hygroscopic salts, metal-organic complex, metal-organic frameworks and covalent organic frameworks) within porous matrices (i.e., aerogels, hydrogels, lms, fabrics and sponges) is of particular interest. Although atmospheric water is considered as a promising solution for the growing scarcity in agriculture, few sorption-based AWGs have been developed for the specic use in solar-powered irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that constructing porous structures is more conducive to microwave absorption (MA) promotion compared with using solid particles under the same amount [27][28][29][30][31][32]. Freeze-drying method is the most common way for constructing porous structures in terms of aerogel and foam sponge.…”
Section: Introductionmentioning
confidence: 99%